Evidence-based Prehospital Management of Severe Traumatic Brain Injury: A Comparative Analysis of Current Clinical Practice Guidelines. (3rd April 2014) - Hoogmartens, Olivier; Heselmans, Annemie; Velde, Stijn Van de; Castrén, Maaret; Sjölin, Helena; Sabbe, Marc; Aertgeerts, Bert; Ramaekers, Dirk
Abstract Objective. This study appraised the completeness and level of evidence behind prehospital recommendations in clinical practice guidelines (CPGs) for management of severe traumatic brain injury (TBI). Differences and similarities in key recommendations for prehospital emergency care were assessed between current CPGs. Methods. A systematic search identified current evidence-based CPGs for the management of severe TBI. The identified CPGs were screened for prehospital recommendations. Finally, an evaluation of the completeness and level of evidence for each of the identified recommendations was carried out. A review of the literature identified additional evidence. Designs of the retrieved publications were considered and classified according to the GRADE levels of evidence. Results. This study identified 12 current CPGs for the management of patients after traumatic brain injury. Of these, twenty-one prehospital recommendations were selected. Only a few CPGs made recommendations on temperature management and ventilation patterns. Statements on prehospital transport and advanced airway management were common to all of the guidelines. Statements on initial treatment demonstrated the greatest variability. The literature review identified several relevant publications not included in the CPGs even after we controlled for the indicated time-intervals of their literature search. In addition, evidence from more recent trials published outside the search-interval of the clinical practice guidelines was found. Conclusions. The use of current guidelines on traumatic brain injury will not always facilitate decisions about best or most appropriate practice for prehospital practitioners. The amount of recommended prehospital interventions varied considerably, and there was large content variation in prehospital recommendations in these guidelines. Not all evidence was taken into account and not all CPGs were up-to-date.